Comparison of Safety and Efficacy Between Clopidogrel and Ticagrelor in Elderly Patients With Acute Coronary Syndrome: A Systematic Review and Meta-Analysis - Zhao, Xiangkai; Zhang, Jian; Guo, Jialin; Wang, Jinxin; Pan, Yuhui; Zhao, Xue; Sang, Wentao; Yang, Kehui; Xu, Fengyang; Xu, Feng; Chen, Yuguo (Frontiers in Pharmacology, 2021)
Background: Dual antiplatelet therapy combining aspirin with a P2Y12-adenosine diphosphate receptor inhibitor is a therapeutic mainstay for acute coronary syndrome (ACS). However, the optimal choice of P2Y12-adenosine diphosphate receptor inhibitor in elderly (age ≥ 65) patients remains controversial. We conducted a meta-analysis to compare the efficacy and safety of ticagrelor and clopidogrel in elderly patients with ACS. Methods: We comprehensively searched in Web of Science, EMBASE, PubMed, and Cochrane databases through 29th March, 2021 for eligible randomized controlled trials (RCTs) comparing the efficacy and safety of ticagrelor or clopidogrel plus aspirin in elderly patients with ACS. Four studies were included in the final analysis. Fixed effects model or random effects model were applied to analyze risk ratios (RRs) and hazard ratio (HRs) across studies, and I2 to assess heterogeneity. Results: A total number of 4429 elderly patients with ACS were included in this analysis, of whom 2170 (49.0%) patients received aspirin plus ticagrelor and 2259 (51.0%) received aspirin plus clopidogrel. Ticagrelor group showed significantly advantage over clopidogrel group concerning all-cause mortality (HR 0.78, 95% CI 0.63–0.96, I2 = 0%; RR 0.79, 95% CI 0.66–0.95, I2 = 0%) and cardiovascular death (HR 0.71, 95% CI 0.56–0.91, I2 = 0%; RR 0.76, 95% CI 0.62–0.94, I2 = 5%), but owned a higher risk of PLATO major or minor bleeding (HR 1.46, 95% CI 1.13–1.89, I2 = 0%; RR 1.40, 95% CI 1.11–1.76, I2 = 0%). Two groups showed no significant difference regarding of major adverse cardiovascular events (MACEs) (HR 1.02, 95% CI 0.64–1.61, I2 = 44%; RR 1.04, 95% CI 0.69–1.58, I2 = 45%). Conclusions: For elderly ACS patients, aspirin plus ticagrelor reduces cardiovascular death and all-cause mortality but increases the risk of bleeding. Herein, aspirin plus ticagrelor may extend lifetime for elderly ACS patients compared with aspirin plus clopidogrel. The optimal DAPT for elderly ACS patients may be a valuable direction for future research.